From deficiency to excess: the impact of iodine excess on reproductive health - Khudair, Aiman; Khudair, Ahmed; Niinuma, Sara Anjum; Habib, Haniya; Butler, Alexandra E. (Frontiers in Endocrinology, 2025)
Iodine is a critical trace element in the human body. It is primarily obtained through dietary sources such as dairy products, seafood, fish, eggs and certain vegetables. Iodine plays an essential role in various bodily functions, most notably in producing the thyroid hormones, triiodothyronine and thyroxine. Additionally, it influences the immune, cardiovascular, reproductive and gastrointestinal systems. Historically, iodine deficiency has been a significant global health issue; however, over the past decade, there has been a rise in iodine excess. This surge has been primarily attributed to inadequate monitoring and over-iodization of salt. Despite the well-documented consequences of iodine deficiency, the ramifications of excessive iodine intake remain underexplored. In view of rising global infertility rates, excess iodine has been linked to significant reproductive health effects. These include decreased sperm count, motility and morphology in males, as well as adverse pregnancy outcomes in females, such as maternal thyroid dysfunction and congenital hypothyroidism. This mini-review aims to collate and analyze current literature pertaining to the effects of iodine excess on reproductive health and shed light on its increasing incidence worldwide. Further research on the biological and clinical effects of iodine excess is required to derive a better understanding of this issue. Given the rising prevalence of iodine excess, it is crucial to raise awareness and implement proactive measures to prevent it from escalating into a major public health crisis in the future.